Integrating High-Throughput Approaches and in vitro Human Trophoblast Models to Decipher Mechanisms Underlying Early Human Placenta Development - Lee, Bum-Kyu; Kim, Jonghwan (Frontiers in Cell and Developmental Biology, 2021)
The placenta is a temporary but pivotal organ that is essential for a healthy pregnancy. It consists of multiple specialized trophoblast cell types that originate from the trophectoderm of the blastocyst stage of the embryo. While dysregulation of proper trophoblast differentiation can lead to pregnancy disorders that affect both the mother and fetus, molecular mechanisms modulating placenta development have been poorly understood, partially due to limited access to the developing placenta and lack of suitable in vitro model systems for the human placenta. Recent success in establishing human trophoblast stem cells has provided a tremendous opportunity in vitro to elucidate the molecular mechanisms by which trophoblast stem cells differentiate into two major cell types (syncytiotrophoblast and extravillous trophoblast) in the human placenta. Notably, advances in high-throughput research methods have enhanced our understanding of placenta development and placenta-associated diseases, such as preeclampsia and intrauterine growth restriction, in concert with functional assays in trophoblast stem cell models. This review summarizes recent findings in trophoblast differentiation and placental development using various omics tools and also discusses future perspectives and challenges in placenta research.